The Challenges of a "Multicultural" Classroom: Some Reflections - Das Gupta, Tania (Atlantis, 2012)
The author reflects on small group work in classes and common challenges encountered in terms of "differences" and "power." She suggests that these challenges may be a product of state multiculturalism discourse and resultant identities. Another dimension of social experience, disability, is also touched on.